Spots Archives, April 1977 to September 1977 (1977)
[00:00:10] KCPR News Promo - Dave Kerley Associate News Director [00:00:32] San Luis Obispo County Band Spring Concert April 14 [00:01:18] Student Health Center Blood Drive Thursday April 14 Chumash Auditorium [00:02:36] Little Orphan Annie Promo Amy [00:03:14] western Program Board [00:03:59] Western Program Board Country Western Dance "Horses are optional" [00:04:48] Cal Poly Penguins Motorcycle club screens On any Sunday [00:05:21] Annual Phone Booth Stuffing Contest [00:05:56] "On Track" Promo "Full length concert recordings" [00:06:43] IRS Blues Autocross - Cal Poly Sports Car Club [00:07:21] Cal Poly Intramurals [00:07:55] Sunday By Request Promo Marv Miller [00:08:35] Chris Sandy's Show Promo [00:09:24] Yahweh Music Show Promo Saturday Morning 6-10AM [00:10:28] SLO Board of Realtors "Speak up on issues to protect rights" [00:11:11] San Luis Obispo County Hotline PSA 544-6162 [00:11:59] Council Exceptional Children Monday April 18th [00:12:44] Veterans Administration On the Job Training [00:13:30] Society for the Advancement of Management (SAM) Bargin Book Sale [00:14:22] SLO Little League Umpire request PSA [00:14:56] Wanda Lust Extravaganza Promo 3-6AM Fridays [00:15:42] Cal Poly Recreation Center Earth Day Festival [00:16:06] ASI Fine Arts Committee "I never sang for my Father" "The Heart is a Lonely Hunter" 7PM Sat [00:17:08] Poly Royal Events Promo by Women's Physical Eduction Dept [00:18:14] Outreach Committee [00:18:40] Peter Stewart Show Promo Wed 10 PM [00:19:14] Poly Royal Live Broadcast Promo Castillo/Conner Friday 6:15PM [00:19:54] Little Orphan Amy Promo Wed 9PM [00:20:20] Power Against Nuclear Power Protest balloon release [00:21:13] SLO Hotline Volunteers request [00:21:37] Cal Poly Music Department Home Concert Sat at 8PM [00:22:24] Jazz with Jeff Promo Wed 7-9PM [00:23:06] Open Channel Mayor Kenneth Swartz May 9th [00:23:40] Cuesta College - Dirk Hamilton - Cinco de Mayo 7PM [00:24:42] "38 Special" Album Giveaway Promo - Cannon Shot [00:25:35] ASI Speakers Forum - George Plimpton Chumash [00:26:23] Bio-Feed Back, Cal Poly Extension [00:27:06] San Luis Film Society May 14-15th 7:30 and 9PM [00:27:44] Newsday Promo Tuesday May 17th [00:28:30] SLO Roadsters Rod-o-Rama Sat May 21 Santa Rosa Park [00:29:09] The ASI Candidates Speak Tues May 10 at 6:15 [00:29:50] KCPR Sports Magazine - Scott Hamilton, Jay Birks Wed 6:15 - Randy Kerdoon [00:30:41] Cal Poly Recereation, Arm Wrestling Tournament, May 17 and 19th 11AM to 12 [00:31:54] Plastics Symposium [00:32:16] Oldies Show Promo, Sat 3-6PM - Gene Mario [00:33:30] Humanites 420X Family Issues May 28 Leon Panetta [00:34:13] SLO Chamber of Commerce [00:34:31] US Friends of China Away all Pests [00:35:17] SLO County Band June 3td [00:35:56] SLO County Band June 3td [00:36:30] CHP "55 MPH Compliance Month" [00:37:02] Gong Radio Special Program June 2 Midnight-3AM [00:38:03] Public Service publicity request promo [00:38:50] Cal Poly Recreation Kite Day [00:39:19] Cal Poly Recreation Kite Day [00:39:39] "On Track" program promo, live recording of ELO, Mon 11PM [00:40:42] Little Orphan Amy Promo [00:41:18] Summer KCPR Promo [00:41:59] Five Summer Hours plus 1, Monday 9AM [00:42:42] On Track promo 1130PM Chris Hillman [00:43:20] Top 27 of 1977 Promo - The Captain [00:44:19] Allan Hancock College Film Festival, 7PM June 11-12 [00:45:09] SLO Police Dept [00:45:48] SLO City Count, Happy Korean Happening [00:46:20] KCPR City Marquis for June 5th [00:47:10] San Antonio Mission 206th Annivesary Fiesta, ON SUNDAY [00:48:05] Girls Softball Benefit [00:48:32] International Womens Year, USC, June 16-19 [00:49:34] KCPR News Promo 91 Newswatch, weekdays at 6PM - Vivi St Amand, Kevin Riggs [00:50:27] KCPR Sports Promo Jay Birks Sports 77 Summer [00:51:13] Dragon Making Contest SLO City/County Libraries, entries before July 9th [00:52:03] SLO Police Dept [00:52:56] Morro Bay Fire Dept, Sunday July 3td, Chicken BBQ, Fire engine restoration [00:53:45] Calif Dept of Forestry, 4th of July fireworks displays Recorded July 5, 1977 [00:54:58] Yahweh Music Promo, Sat 9-noon [00:55:38] "Sunday By Request" Summer months Promo - January Lee [00:56:40] Big Bands promo, Sundays from 3 to 6. - Groove Merchant [00:57:18] City Council Coverage Promo evey other Tuesday at 7PM [00:57:52] The Sheriff Promo Monday 9 to Noon - Jay Birks Recorded July 7, 1977 [00:58:35] Sunday By Request Promo - January Lee [00:59:35] Associated Students, Aug 31 Football Season Ticket Renewal [01:00:16] Sunday By Request Promo - January Lee [01:01:05] Kevin Riggs Show Promo, T-Th 6-9AM - Kevin Riggs [01:02:24] The Sherrif promo, Monday 9-Noon - Jay Birks [01:03:05] An Hour With promo Wed 11PM - Jay Birks [01:03:58] 91 Entertainment Thurs 6:15PM [01:04:26] Big Bands and All that Jazz promo, Sundays from 3 to 6. [01:05:07] Jack Beardwood Wed Night Jazz ,Wed 6:15 -9PM [01:05:48] CA Medical Assoc - don't shake kids [01:06:28] SLO County Fair, Annual Talent Show Auditions, July 31 [01:07:43] Project Sort Recycling on Garbage Collection Day [01:08:18] SLO County Fair deadlines Recorded 8/8/1977 [01:09:05] Overland Express [01:09:11] KCPR Sports Promo, Babe Ruth - Jay Birks [01:09:40] Yosemite Hall, Car Wash, Sat 10am - 4PM [01:10:28] 3th Annual Skateboarding championship [01:11:38] License Renewal Announcement [01:12:22] California Lung Association, smoking, Batman and Robin [01:13:40] SLO County Headstart, special needs children [01:14:41] News Promo, Summer 1977, Monday and Friday 6PM, 91 Newswatch - Kevin Riggs [01:15:28] News Promo, George Carlin, 91 Newswatch Monday and Friday 6PM - Vivi St Amand [01:16:32] Clark Savage Promo, Friday 6-9AM, Robb,9 to Noon, Sheriff Noon-3 [01:18:11] Puppeteers of America, Aug 12-20 [01:19:16] Puppeteers of America Recorded Aug 8, 1977 [01:20:11] Cal Poly Extension, [01:20:42] ASI Films Committee, "Bang the drum Slowly" Friday at 7 and 9 [01:21:13] People Generating Energy, Aug 5th, The Last Resort [01:21:42] 91 Entertainment, Thurs 6:15PM Recorded 8/19/77 [01:22:12] Special Events Committee [01:22:41] The Sherrif, 9-Noon on Monday, tells the time and temperature [01:23:53] Associate Students season football ticket renewal reminder [01:24:47] The Sherriff Promo - Friday Noon-3 [01:25:47] Cuesta Courgar Football Promo - Fall 1977 - Jay Birks [01:26:30] Zion Concerts Presents Parable in Concert [01:27:16] SLO Environmental Center Promo [01:28:03] SLO Rugby Club 1st Annual Day in the Sun Relay [01:29:06] California Medical Association - Hearing Loss [01:29:50] Voice of Cal Poly [01:29:59] KCPR Promo - Captain and Tennile Legal ID [01:30:12] KCPR Promo - Roy Clark Legal ID [01:30:15] KCPR Promo - Roy Clark Not-Legal ID [01:30:25] KCPR Promo - Captain and Tennile Legal ID Recorded 9/13/77 [01:30:32] 91 Entertainment Promo [01:31:21] Women's Resource Center Poetry Contest [01:32:18] KCPR - The Pacific Concert 3pm-6pm [01:32:53] SLO City Council Meeting - Tuesday 7pm [01:33:12] Building Permits - SLO City Hall to SLO Homeowners [01:34:04] Kappa Delta Sorority - Country Welcome Back Dance Recorded 9/24/77 [01:34:47] ASI Finance Committee [01:35:19] Mat Pica Pi - Annual Events Calendar [01:36:02] Mat Pica Pi - 21st Annual Events Calendar [01:37:00] Cal Poly Ski Club - 1st Meeting in Chumash [01:37:42] Omega Psi Phi - Disco Dance with the Stepping Queues(?) [01:38:43] Cal Poly Placement Center - Open House in Admin Building [01:39:27] Poly Phase Book Exchange M-F 9-4 in Mustang Lounge [01:40:04] KCPR Promo - "Better Sound" [01:40:35] KCPR Promo - The Pacific Concert Classical Music [01:41:09] KCPR Sports Promo [01:42:00] SLO City Council Meeting Every Other Tuesday 7pm [01:42:18] Family Services Center - Marriage Enrichment Workshop [01:43:02] SLO Pilots Association - Air and Auto Show featuring Antique and Experimental Aircrafts [01:43:50] SLO Recreation Department - Folk Dancing Classes [01:44:57] Pacific Telephone Center Promo [01:46:10] Pacheco Elementary PTA Swap Meet [01:47:01] SLO Film Society - Children of Paradise [01:47:48] SLO County League of Women Voters - General Meeting